Trichoepithelioma – diagnostic difficulties - Borzęcki, Adam; Szponar-Bojda, Anna; Szubstarski, Franciszek (Dermatology Review/Przegląd Dermatologiczny, 2013)
Trichoepithelioma is a benign skin tumour derived from hair follicles. Trichoepithelioma usually occurs on the face as a single lesion or as multiple changes in a genetically determined disorder. Trichoepithelioma and basal cell carcinoma can have similar clinical and histopathological features. In rare cases, neoplastic transformation of Trichoepithelioma can be observed. Moreover, some authors suggest that the presence of Trichoepithelioma s can be a predisposing factor for the development of basal cell carcinoma. These facts underline the significance of the early and accurate diagnosis of suspicious lesions.